2011
DOI: 10.5551/jat.5702
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of 5'-UTR Thymidylate Synthase Polymorphism with 677C→ T Methylene Tetrahydrofolate Reductase and 66A→ G Methyltetrahydrofolate Homocysteine Methyl-transferase Reductase Polymorphisms Determine Susceptibility to Coronary Artery Disease

Abstract: Dietary folate status and TYMS 5'-UTR 28bp tandem repeat polymorphism are important effect modifiers of CAD risk associated with genetic variants in remethylating genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…MTHFR 1298AC/TYMS 2R/2R genotypic combination is associated with reduced risk factor for DS in Italian population [8]. In another study, the 2R/2R genotype has been reported to be protective for coronary artery disease [35] and in drug response for certain cancer treatment [27,36,37] via interaction with folate intake. Further in a study of Artificial neural network analysis by Coppede et al, revealed TYMS 2R/3R genotype is closely connected with a condition of being mothers of DS and TYMS 3R/3R genotype connected with control mothers [38].…”
Section: Discussionmentioning
confidence: 99%
“…MTHFR 1298AC/TYMS 2R/2R genotypic combination is associated with reduced risk factor for DS in Italian population [8]. In another study, the 2R/2R genotype has been reported to be protective for coronary artery disease [35] and in drug response for certain cancer treatment [27,36,37] via interaction with folate intake. Further in a study of Artificial neural network analysis by Coppede et al, revealed TYMS 2R/3R genotype is closely connected with a condition of being mothers of DS and TYMS 3R/3R genotype connected with control mothers [38].…”
Section: Discussionmentioning
confidence: 99%
“…4A. Disruption of cysteine and methionine metabolism also influences oxidative stress through involvement of metabolic intermediates causing endothelial cell damage or inflammation (29). NAD metabolism is a major consequence of reactive oxygen species (ROS) generation, which has been associated with androgenic effects on prostate tissue (30).…”
Section: Metabolic Pathway Alterations In Pct-mentioning
confidence: 99%
“…COMT supports the production of homocysteine 9) , predisposing subjects to coronary artery disease 15) , internal carotid artery stenosis and occlusion 16) , by thickening the arterial wall and narrowing the vascular radius 17) . Thus, it is conceivable that higher levels of COMT activity may result in higher total plasma homocysteine (tHcy) levels.…”
Section: Discussionmentioning
confidence: 96%